NUCLEATION PROBLEMS OF THE MARTENSITIC TRANSFORMATION IN STEEL - Victor Nikolayevich Pustovoyt; Yury Vyacheslavovich Dolgachev (Advanced Engineering Research)
A review of papers on martensitic transformations is presented. To clarify the martensite nucleation mechanism in iron-carbon steels on the basis of the currently established understanding is the main purpose of the review. The martensitic transformation is one of the main types of phase transformations in the solid state which is observed in materials with different nature. Need for a thorough and comprehensive analysis of the structural states formed during steel quenching is determined by its scientific and applied relevance. The martensitic transformation models are presented and critically discussed. The transformation features inherent martensite nucleation in steel are marked. The specific model reconstructions of crystal lattices are shown. The energy barrierless martensite nucleation model is considered in the work. As follows from the analysis of the spatial configurations formed by the martensite plates, it is concluded that they are defined more by the general patterns of the crystal growth than by the interaction between the elastic fields of the colliding plates. It is noted that the generalization and projection of the obtained results on nonferrous and rather exotic model alloys for steel are incorrect. It is concluded that the mechanism of martensite nucleation in the iron-carbon steel is still not fully disclosed.